Blood biochemical parameters during bovine endotoxemia and after i/v infusion of hypertonic saline and plasmex-D-40 - SINGH, D V; SINGH, R V; SODHI, S P S (The Indian Journal of Animal Sciences, 2014)
Two groups of 5 animals each were subjected to endotoxic shock to investigate the biochemical effects of i/v infusion of hypertonic saline and dextran-40 by i/v infusion of E. coli endotoxin @ 5 mg/kg bw/hr for 3 hr. Group 1 animals which were left untreated afterwards and were observed for next 4 hr showed a significant (P<0.05) hypoprotinemia, hypoalbuminemia alongwith hypoglycacmia, hypochloraemia and decrease in plasma creatinine. The plasma globulins and other proteins altered nonsignificantly. Group 2 animals had the same protocol till 3 hr and were immediately treated with i/v infusion of 7.2% hypertonic saline solution @ 4 ml/kg bw in 6.5 min followed by dextran-40 solution @ 10 mil kg bw. Unlike the animals of group 1, the animals of this group did not suffer from hypoglycaemia till 6 hr showing beneficial effects of dextran-40 which apart from improving haemodynamics by increasing colloidal osmotic pressure also improved the glucose levels in blood as indicated by higher values observed in this group throughout the investigation in comparison to group 1. However, there was hypoalbuminemia, and hypochloraemia was also observed in this group. Total protein, globulin and other proteins and creatinine varied only non-significantly in this group.